Beneficial use of sludge from water treatment plants as a multiple resource: Potential and limitations - Messa, Gabriela Nakayama [UNESP]; Jesus, Amanda Maria Dantas de [UNESP]; Fiore, Fabiana Alves [UNESP] (Elsevier, 2025)
The increasing and continuous generation of water treatment plant sludge (WTPS) is still an under-recognised problem, although in most countries the inappropriate disposal of WTPS into watercourses has a negative impact on the environment. The need to incorporate circular economic principles in the management of this waste has stimulated studies on the reintroduction of WTPS into the production chain, but these investigations generally evaluate specific processes. The aim of this research was to identify the potential and limitations of WTPS reuse. Therefore, a systematic literature review was carried out using the archival search method, which resulted in the analysis of 106 selected articles. The results show that the beneficial use of WTPS in the manufacture of construction products and as inputs for chemical processes are the most studied applications. This can be explained by sludge's composition that consists of more than 80% by mass of the elements: silicon, aluminum, iron and calcium. It should be noted that the predominance of these elements is related to the type of input used in water purification and the characteristics of the raw water collected. The mineralogical composition of WTPS is seasonally predominated by quartz and kaolinite. These residues also contain heavy metals especially such as barium, chrome, lead and mercury, and microorganisms such as proteobacteria, firmicutes and cyanobacteria, presenting potential risks to human health and the environment, and demanding special care in the management and beneficial uses. The lack of standardization and studies that address environmental and economic viability are research gaps in this area.
Keywords: Drinking water treatment sludge; Health and environment impacts; Sludge composition